Frans Hals: Iconography – Technique – Reputation - Abraham, Liesbeth; Halm, Koos Levy-van; Biesboer, Pieter; Middelkoop, Norbert E; Kleinert, Katja; Hartwieg, Babette; Mahon, Dorothy; Centeno, Silvia; Groves, Roger; Anisimov, Andrei; Dik, Joris; Grimm, Claus; et al. (Frans Hals Studies, 2024)
Frans Hals (1582/83-1666) is rightfully considered one of the most important seventeenth-century Dutch painters. His portraits are admired for their virtuoso brushwork and their seemingly spontaneous character. This volume, with fourteen contributions by twenty-six specialists on Hals’s paintings and his artistic network in Haarlem and beyond, presents a rich palette of new research. The authors introduce subjects such as the artist's clientele - from clergymen and fellow painters to governors of charitable institutions - as well as stylistic and technical aspects of individual paintings. Results of recent restorations are discussed, but also how advanced digital technologies contribute to our understanding of the painter's style and artistic development. A final section is dedicated to the rediscovery of Frans Hals in the second half of the nineteenth century and to the following art historical debate among connoisseurs about the artist’s oeuvre. Frans Hals: Iconography - Technique - Reputation is the first volume in the Frans Hals Studies book series and is richly illustrated with close to two hundred colour illustrations.